Perception Of Watukosek Village Farmers Towards Babang Laper Youtube Channel - Saputra, Muhammad Sulung; Rochmaniah, Ainur (Universitas Muhammadiyah Sidoarjo, 2024)
This research aims to determine farmers’ perceptions of the use of digital information, espeTcially via the YouTube platform, on farming in Watukosek Village, Pasuruan Regency. The growth of digital information technology has created new opportunities for farmers to increase productivity and market their agricultural products. Therefore, this research focuses on the impact and effectiveness of using these digital platforms in supporting agricultural activities at the local level. The research was conducted using a qualitative approach with descriptive methods. The theory used is S-O-R (Stimulus Organism Response), which was first discovered by Hovland (1953). Data collection techniques were carried out using interviews, observation and documentation. The results of research conducted at the research location, the use of digital media shows significant actions, reactions and perceptions after viewing the YouTube content “Babang Laper” which has diverse audience characteristics in Watukosek Village. Conclusion The importance of digital literacy for farmers, as it opens the door for them to access the latest information on best agricultural practices.